CompTIA A+ certification 901 : the total course (Packt Publishing, 2017)
"Everything you need to pass the CompTIA A+ 220-901 Exam, from Mike Meyers, CompTIA expert and bestselling author. This is the first of a two course series for CompTIA A+ and is designed to prepare you to take and pass the CompTIA A+ 220-901 exam. To become fully A+ certified you will need to pass both the 220-901 and 220-902 exams."--Resource description page